Auctioning out education: On exogenous privatisation through public procurement. (January 2021) - Holmqvist, Diana; Fejes, Andreas; Nylander, Erik
Privatisation of public education is becoming more and more common across the world. As much current research presupposes causal links between the degree of privatisation and issues of competition and student's free choice, we see a need for research on other ways of organising the presence of private providers in public education. In this article, we study how two Swedish municipalities use public procurement to contract private providers and organise adult education. Interestingly, we find that competition is more heavily at play in the municipality that outsources half of its adult education, than in the municipality that outsources all adult education. We view these findings as vital for understanding how education is being outsourced to private providers and for furthering the discussion on the consequences of the ongoing privatisation of education.